A Project Report On Accident Alert System For Automobiles Using GPS and GSM - DILIP D ,ISASC K PHILIP,KIRAN SINGH R and NITYANAN U SALUNKE (2011)
INTERNAL GUIDE : Muthaiah U EXTERNAL GUIDE : Avayambal K USN NO : 1MJ08CS022, 1MJ08CS033,1MJ08CS036 and 1MJ08CS055 CARRIED OUT AT : Intelnet Technologies Balaji Nagar Mallath Halli Post Bangalore-560 056 ACC NO : PR1843 Project Report CD No : RC41
Keywords: Accident Alert System